2017
DOI: 10.4172/2161-1068.1000246
|View full text |Cite
|
Sign up to set email alerts
|

Researching the Changes of Serum Procalcitonin Levels in Ventilator-Associated Pneumonia Patients

Abstract: Background: Ventilator-Associated Pneumonia (VAP) is the most common hospital acquired infection in the intensive care unit with high mortality rate. The role of the clinical symptoms for the VAP diagnosis is limited. Procalcitonin (PCT), currently interested biomarkers, plays an important role in the diagnosis and the outcome of the ventilator-associated pneumonia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…These findings suggest that combining cohorts based on HELICS and CPIS may be reasonable for meta-analysis or population studies, but the same may not be true for studies based on CDC/NHSN criteria as the diagnostic agreement is poor. Moreover, it is recommended that studies report serum procalcitonin values to better refine their data sets to optimize data utility as diagnostic algorithms evolve to best facilitate future meta-analyses and as procalcitonin may correlate with mortality [62]. Lastly, this data highlights how little progress these complicated VAP diagnostic algorithms have made beyond that of the historical and simple Johanson criteria.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that combining cohorts based on HELICS and CPIS may be reasonable for meta-analysis or population studies, but the same may not be true for studies based on CDC/NHSN criteria as the diagnostic agreement is poor. Moreover, it is recommended that studies report serum procalcitonin values to better refine their data sets to optimize data utility as diagnostic algorithms evolve to best facilitate future meta-analyses and as procalcitonin may correlate with mortality [62]. Lastly, this data highlights how little progress these complicated VAP diagnostic algorithms have made beyond that of the historical and simple Johanson criteria.…”
Section: Discussionmentioning
confidence: 99%
“…These ndings suggest that combining cohorts based on HELICS and CPIS may be reasonable for meta-analysis or population studies, but the same may not be true for studies based on CDC/NHSN criteria as the diagnostic agreement is poor. Moreover, it is recommended that studies report serum procalcitonin values to better re ne their data sets to optimize data utility as diagnostic algorithms evolve to best facilitate future meta-analyses and as procalcitonin may correlate with mortality [82]. Lastly, this data highlights how little progress these complicated VAP diagnostic algorithms have made beyond that of the historical and simple Johanson criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most studied biomarkers for VAP diagnosis and prognosis is serum procalcitonin. Serum procalcitonin concentration >0.5 ng/ml has been reported to have a diagnostic sensitivity and speci city of 68.25% and 89.83% respectively [67]. Others have reported that the optimal threshold value VAP diagnosis on day 1 was 5.0 ng/ml (sensitivity 91%, speci city 71%) [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation